Taking on the Corporate Determinants of Ill-health and Health Inequity: A Scoping Review of Actions to Address Excessive Corporate Power to Protect and Promote the Public's Health - Benjamin Wood; Jennifer Lacy-Nichols; Gary Sacks (Kerman University of Medical Sciences, 2023)
Background  In many sectors of the economy, for-profit business corporations hold excessive power relative to some governments and civil society. These power imbalances have been recognised as important contributors to many pressing and complex societal challenges, including unhealthy diets, climate change, and widening socio-economic inequalities, and thus pose a major barrier to efforts to improve public health and health equity. In this paper, we reviewed potential actions for addressing excessive corporate power.Methods  We conducted a scoping review of diverse literature (using Scopus, Web of Science, HeinOnline, and EBSCO databases), along with expanded searches, to identify state and collective actions with the potential to address excessive corporate power. Actions were thematically classified into overarching strategic objectives, guided by Meagher's '3Ds' heuristic, which classifies actions to curb corporate power into three groups: dispersion, democratisation, and dissolution. Based on the actions identified, we proposed two additional strategic objectives: reform and democratise the global governance of corporations, and strengthen countervailing power structures.Results  We identified 178 documents that collectively cover a broad range of actions to address excessive corporate power. In total, 18 interrelated strategies were identified, along with several examples in which aspects of these strategies have been implemented.Conclusion  The proposed framework sheds light on how a diverse set of strategies and actions that seek to address excessive corporate power can work synergistically to change the regulatory context in which corporations operate, so that broader societal goals, including health and equity, are given much greater prominence and consideration vis-à-vis powerful corporate interests.